Why was rape regulation omitted from the first EU Directive on violence against women? - Mireia Brunet Villarejo (Quaderns IEE, 2025)
In May 2024, the European Parliament and the Council adopted the first-ever European Union (EU) Directive specifically aimed at combating violence against women and domestic violence. While recent years have seen a growing momentum in addressing these issues at both European and national levels, existing measures remain insufficient to effectively prevent such violence and protect its victims. To address these shortcomings, the EU-27 have established minimum standards for defining and sanctioning certain criminal offenses related to gender-based violence.